Relevansi Konversi SKS Mata Kuliah Dalam Program Pertukaran Mahasiswa Merdeka 2 Mahasiswa PAI UNP (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Facing the rapid development of the times, the government of the Republic of Indonesia has swiftly kept pace by launching the Independent Learning Campus policy by the Ministry of Education and Culture. One of the superior programs implemented by the Islamic Religious Education study program at Padang State University is the Independent Student Exchange (PMM). In its implementation, there are several technical differences that occur because the Ministry of Education and Culture gives full authority to universities to implement this policy, while the time given to prepare is very limited. One of the technical differences that the author raises in this research is related to the relevance of converting course credits from the receiving university to the originating university. This research uses a qualitative method with a case study approach. The data sources in this research were informants consisting of 3 PAI lecturers and 10 alumni of PMM 2 PAI FIS UNP study program. Meanwhile, the documents used are proof of student learning outcomes from the recipient university. Data collection techniques through observation, interviews and documentation. Data were analyzed through data reduction, data presentation and drawing conclusions. Data validity techniques use source triangulation and engineering triangulation. The research results showed that of the 10 PMM 2 alumni students from the PAI FIS UNP study program, 2 of them took cross-majors, 3 took mixed majors, and 5 people remained in the PAI major. The results of the interviews show that the courses converted from the recipient PT to the original PT were all relevant because all of the alumni took majors that were still relevant to the PAI FIS UNP study program.
Keywords: Relevance; SKS conversion; Merdeka 2 student exchange program